2021
DOI: 10.3390/su13168850
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organic Traffic of Crowdsourcing Platforms on Airlines’ Website Traffic and User Engagement

Abstract: With airline companies increasingly relying on crowdsourcing websites to deploy their digital marketing strategies, marketeers and strategists seek to acquire an understanding of the factors affecting airlines’ organic traffic and user engagement. Such an understanding is acquired through the consideration of variables that influence a company’s organic traffic and user engagement and their correlation to each other. A three-stage data-driven analysis is used to examine the correlation between the foregoing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The main prerequisites were the use of Facebook and Instagram for their social media promotion as well as the use of their website for the digital promotion of their services. Following several research recommendations, the authors chose seven logistics websites, as that is considered an adequate number for the type of analysis that this research performs and depicts a sufficient number to produce results for the logistics sector [9,14].…”
Section: Web Analytics Key Performance Indicators (Kpis) and Corporat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main prerequisites were the use of Facebook and Instagram for their social media promotion as well as the use of their website for the digital promotion of their services. Following several research recommendations, the authors chose seven logistics websites, as that is considered an adequate number for the type of analysis that this research performs and depicts a sufficient number to produce results for the logistics sector [9,14].…”
Section: Web Analytics Key Performance Indicators (Kpis) and Corporat...mentioning
confidence: 99%
“…The procedure of studying the behavior of users on a website is known as web analytics [2,3]. Previous studies have shown that logistics websites' brand name, as well as the digital marketing strategy, can be dramatically improved by the correct implementation of web analytics [4,5,9]. Key performance indicators are web analytics that have been extracted from the examined websites and have been utilized quantitatively [50].…”
Section: Web Analytics Key Performance Indicators (Kpis) and Corporat...mentioning
confidence: 99%
“…As profit margins are very low, especially during the COVID-19 pandemic, digital marketing advertisements are frequently employed in the airline sector, which is one of the most competitive industries [26]. The quality of the services offered on the airline businesses' websites, along with their alignment with the intended consumers, impact website traffic, user engagement, and visibility [2,25]. Multiple findings demonstrate the need of creating successful advertising with the help of neuromarketing, which has a good influence on user engagement and visibility [27,28].…”
Section: Digital Promotion Of Airlines' Websitesmentioning
confidence: 99%
“…They have created websites to assist their operations, but a large number are unaware of how competitive their websites are [1]. Airline developers, marketers, and strategists, as well as the aviation sector in general, can employ a variety of tactics to improve their websites' customer engagement [2], brand name [3], and profitability [3,4]. Furthermore, the numerous methods of online payment that websites provide along with their goods or services create value for such businesses [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation